The application of standards and recommendations to clinical ethics consultation in practice: an evaluation at German hospitals - Schochow, Maximilian; Rubeis, Giovanni; Steger, Florian (Science and engineering ethics, 2017)
The executive board of the Academy for Ethics in Medicine (AEM) and two AEM working groups formulated standards and recommendations for clinical ethics consultation in 2010, 2011, and 2013. These guidelines comply with the international standards like those set by the American Society for Bioethics and Humanities. There is no empirical data available yet that could indicate whether these standards and recommendations have been implemented in German hospitals. This desideratum is addressed in the present study. We contacted 1.858 German hospitals between September 2013 and January 2014. A follow-up survey was conducted between October 2014 and January 2015. The data of the initial survey and the follow-up survey were merged and evaluated. The statements of the participants were compared with the standards and recommendations. The standards of the AEM concerning the tasks of clinical ethics consultation (including ethics consultation, ethics training and the establishment of policy guidelines) are employed by a majority of participants of the study. Almost all of these participants document their consultation activities by means of protocols or entries in the patient file. There are deviations from the recommendations of the AEM working groups regarding the drafting of statutes, activity reports, and financial support. The activities of clinical ethics consultation predominantly comply with the standards of the AEM and recommendations for the documentation. The recommendations for evaluation should be improved in practice. This applies particularly for activity reports in order to evaluate the activities. Internal evaluation could take place accordingly.
Gesehen am 12.05.2021